2004
DOI: 10.1111/j.1467-9663.2004.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

MAPPING INNOVATION: REGIONAL DIMENSIONS OF INNOVATION AND NETWORKING IN THE NETHERLANDS1

Abstract: The paper addresses spatial patterns of innovation and partnership in innovation processes in the Netherlands, building on the Netherlands' part of the Community Innovation Survey, conducted by Statistics Netherlands. Innovation is analysed from a system perspective, addressing both input factors (education levels of human resources and R&D), throughput factors (partnership with regionally, nationally and internationally based partners) and output factors (results in terms of the launching of new products on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…It was confirmed that greater diversification of the innovation activities is driven by allocation of sufficient resources for R&D for innovations. This finding is supported, especially by the literature for product innovation [13]. On the other side, the diversification of the collaboration for innovation and of the information sources in companies are findings that are in line with the literature on open innovation and open collaboration principles [7,12].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…It was confirmed that greater diversification of the innovation activities is driven by allocation of sufficient resources for R&D for innovations. This finding is supported, especially by the literature for product innovation [13]. On the other side, the diversification of the collaboration for innovation and of the information sources in companies are findings that are in line with the literature on open innovation and open collaboration principles [7,12].…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, some of these studies used R&D (research and development) expenditure as principle measure of innovation, which is criticized in the later literature. In particular, R&D expenditure could be correlated to certain innovation types, such as to product innovation, as shown for the manufacturing companies from Netherlands [13]. As stated in the Oslo Manual, the measures of innovation input, although related to technical change, are not direct measures for innovation output.…”
Section: Setting the Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…(2006) claim that social (trust) relationships are highly pastdependent -even if the market relationships are extensive and even crossborder. De Bruijn (2004) argues along the same lines. International relation-ships do not hold back an embeddedness within a specific region.…”
Section: Logit Analysismentioning
confidence: 82%
“…Some studies map and investigate various regional dimensions of the innovative process (Pinto, 2009;Gössling and Rutten, 2007;De Bruijn, 2004) while others map regional innovation patterns and categorize regions according to their modes of performing different phases in the innovation process (Capello and Lenzi, 2013;Camagni and Capello, 2013). These studies investigate regional dimensions of innovation processes and innovation outcomes (e.g.…”
Section: Innovation In the Transport Sector In Europementioning
confidence: 99%